Man-Machine Interactions 5 5th International Conference on Man-Machine Interactions, ICMMI 2017 Held at Kraków, Poland, October 3-6, 2017 (Advances in Intelligent Systems and Computing,, 2018)
This Proceedings book provides essential insights into the current state of research in the field of human-computer interactions. It presents the outcomes of the International Conference on Man-Machine Interactions (ICMMI 2017), held on October 3-6, 2017, in Cracow, Poland, which offers a unique international platform for researchers and practitioners to share cutting-edge developments related to technologies, algorithms, tools and systems focused on the means by which humans interact and communicate with computers. This book is the 5th edition in the series and includes a unique selection of high-quality, original papers highlighting the latest theoretical and practical research on technologies, applications and challenges encountered in the rapidly evolving new forms of human-machine relationships. Major research topics covered include human-computer interfaces, bio-data analysis and mining, image analysis and signal processing, decision support and expert systems, pattern recognition, algorithms and optimisations, computer networks, and data management systems. As such, the book offers a valuable resource for researchers in academia, industry and other fields whose work involves man-machine interactions.